Social cognition and interactive training for first-episode, drug-naïve MDD patients - Li, Jiaxin; Li, Ru; Li, Dazhi; Ji, Shiyi Suzy; Luo, Xingguang; Zhang, Yong (Frontiers in Psychiatry, 2025)
ObjectiveThis study aimed to explore the impacts of social cognition and interaction training (SCIT) on serum brain-derived neurotrophic factor (BDNF), glial cell line-derived neurotrophic factor (GDNF) levels, and psychosocial function in first-episode, drug-naïve (FEDN) major depressive disorder (MDD) patients.MethodsIn this 8-week randomized controlled trial (RCT), 45 MDD patients were assigned to SCIT group and 39 to cognitive behavioral therapy (CBT) group. The 17-item Hamilton Rating Scale (HDRS-17) and the Functioning Assessment Short Test (FAST) were performed to measure depressive symptoms and functional impairment severity, respectively. We also collected blood samples for serum BDNF/GDNF level detection.ResultsCompared to CBT, SCIT demonstrated significantly greater improvements in total FAST scores (F (1,82) = 109.21, p < 0.001, ηp2 = 0.57); especially in occupational (F (1,82) = 16.69, p < 0.001, ηp2=0.17); cognitive (F (1,82) = 103.51, p < 0.001, ηp2=0.56), and interpersonal relationship domains (F (1,82) =65.07, p < 0.001, ηp2=0.44). Changes in serum GDNF levels were positively associated with changes in autonomy (r (40) = 0.32, 95% CI = [0.02, 0.57], p = 0.038), and financial domains (r (40) = 0.44, 95% CI = [0.15, 0.65], p = 0.004) in SCIT group.ConclusionImprovements in social function through SCIT can be effectively generalized to MDD patients. Moreover, improved GDNF levels were associated with improvements in specific aspects of social functioning post-SCIT.